Revision of black fungus gnat species (Diptera, Sciaridae) described from the Hawaiian Islands by D.E. Hardy and W.A. Steffan, and a contribution to the knowledge of the sciarid fauna of the Galápagos Islands - Mohrig, Werner; Kauschke, Ellen; Broadley, Adam (Zootaxa, 2019)
On the Hawaiian Islands 22 sciarid species were detected, belonging to the following ten genera: Austrosciara Schmitz & Mjöberg, Bradysia Winnertz, Corynoptera Winnertz, Cratyna Winnertz, Epidapus Haliday, Hyperlasion Schmitz, Lycoriella Frey, Phytosciara Frey, Pseudolycoriella Menzel & Mohrig and Scatopsciara Edwards. The revision resulted in new combinations for the following five species: Austrosciara hawaiiensis (Hardy) comb. n., Corynoptera prominens (Hardy) comb. n., Cratyna adrostylata (Hardy) comb. n., Cr. longicosta (Hardy) comb. n., and Scatopsciara hoyti (Hardy) comb. n. Eight species were declared as new synonyms: Bradysia bishopi Steffan, 1973 = B. centidens Vilkamaa, Hippa & Mohrig, 2012 syn. n.; B. crassicornis (Skuse, 1890) = B. molokaiensis (Grimshaw, 1901) syn. n. and = B. aspercera Mohrig, 2016 syn. n.; B. radicum (Brunetti, 1912) = B. spatitergum (Hardy, 1956) syn. n.; Corynoptera prominens (Hardy, 1956) = C. gladiota Mohrig, 2004 syn. n.; Cosmosciara hartii (Johannsen, 1912) = Plastosciara (Plastosciara) latipons Hardy, 1956 syn. n.; Hyperlasion wasmanni (Schmitz, 1918) = Scythropochroa magnisensoria Hardy, 1956 syn. n.; and Scatopsciara hoyti (Hardy, 1956) = Sc. spiculata Vilkamaa, Hippa & Mohrig, 2012 syn. n. These four species are new reports for Hawai‘i, three of them are new to science: Epidapus pallidus (Séguy), Pseudolycoriella nigrofemoralis Mohrig, Kauschke & Broadley sp. n., Scatopsciara hardyi Mohrig, Kauschke & Broadley sp. n. and Sc. steffani Mohrig, Kauschke & Broadley sp. n. A lectotype was designated for Bradysia radicum (Brunetti) in order to fix the name. All new and revised species are figured. The species Bradysia bishopi Steffan, 1973, B. ocellaris (Comstock, 1882), B. radicum (Brunetti, 1912), Cosmosciara hartii (Johannsen, 1912), Pseudolycoriella planiforceps (Steffan, 1971) and Scatopsciara steffani Mohrig, Kauschke & Broadley sp. n. are reported from the Galápagos Islands.